Self-knowledge - Hatzimoysis, Anthony (Oxford : Oxford University Press, 2011)
What does it mean to know oneself? What makes self-knowledge such an intriguing issue? This collection of essays offers lucid and well-argued answers, which enhance our understanding of the nature and the limits of knowledge of our own beliefs and desires.
Description based on online resource; title from PDF title page (viewed on May 11, 2011).
Includes bibliographical references and index.
Keywords: Self-knowledge, Theory of